Pengaruh Corporate Social Responsibility (CSR), dan Kualitas Produk Terhadap, Citra Bank dan Keputusan Menabung di BNI Syariah Kota Kediri - Djunaedi . (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2016)
This research talked about the client decision to save on BNI Sharia in Kediri Town ofEast Java. This study was focused on bank image improvement model and Saving Decisionbased on CSR, and Product Quality. From the testing results on the model in this research,by using random sampling, structural equation model (SEM) analysis, and the assistancesoftware Amos 20, on 150 respondents, it was able to explain the relationship betweenCSR, Product Quality, and Bank Image on the Saving Decision at Bank BNI Sharia inKediri Town of East Java. In this research, it was obtained a strong influence of CSR onBank Image, amounting to 0.286, and a strong influence of the bank image on the clientsaving decision, that is of 0.780, this case showed that, with the rise of CSR, it will raisethe Bank Image, which in turn raised the Decision Saving of clients. In this research, italso obtained a strong influence of product quality on the Bank Image, amounting to 0.327,this case showed that, with good product quality, it will raise the Saving Decisions ofclients, through Bank Image. While the correlation between CSR and saving decision wasinsignificant.Keywords: CSR, Product Quality, Bank Image, Saving Decision